Answer:
No solution
Explanation:
7( r - 2 ) - 9(r - 1) = 3 ( 5 - r ) + ( r - 8 )
Distribute 7 through the parentheses
7r - 14 - 9(r - 1 ) = 3( 5 - r ) + ( r - 8)
Distribute -9 though the parantheses
7r - 14 - 9r + 9 = 3(5 - r ) + ( r - 8)
Distribute 3 through the parantheses
7r - 14 - 9r + 9 = 15 - 3r + r - 8
When there is (+) in front of an expression in parentheses, the expression remains the same
7r - 14 - 9r + 9 = 15 - 3r + r - 8
Collect like terms
7r - 9r - 14 + 9 = 15 - 3r + r - 8
-2r - 14 + 9 = 15 - 3r + r - 8
Calculate
-2r- 5 = 15 - 3r + r - 8
Subtract the number
-2r - 5 = 7 - 3r + r
Collect like terms
-2r - 5 = 7 - 2r
Cancel equal terms on both sides of the equation
- 5 = 7
The statement is False for any value of X.
Hence, there is no solution.
Hope this helps...
Good luck on your assignment...